Veterinary Research Communications An International Journal Publishing Topical Reviews and Research Articles on all Aspects of the Veterinary Sciences - Dalziel, Robert G.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
Veterinary Research Communications publishes fully refereed research articles and topical reviews on all aspects of the veterinary sciences. Interdisciplinary articles are particularly encouraged, as are well argued reviews, even if they are somewhat controversial. The journal is an appropriate medium in which to publish new methods (with evidence of application), newly described diseases and new pathological findings, as these are applied to animals. The material should be of international rather than local interest. As it deliberately seeks a wide coverage, Veterinary Research Communications provides its readers with a means of keeping abreast of current developments in the entire field of veterinary science.
Keywords: Veterinary medicine; Zoology; Zoology; Veterinary Medicine/Veterinary Science